2019
DOI: 10.1155/2019/7201562
|View full text |Cite
|
Sign up to set email alerts
|

IGHG1 Regulates Prostate Cancer Growth via the MEK/ERK/c-Myc Pathway

Abstract: Increasing evidence indicates that immunoglobulins are important for the regulation of various cancers including prostate cancer (PCa). However, the underlying mechanisms of IgG regulated PCa development remain to be further explored. Here, we demonstrated that IgG1 heavy chain (IGHG1) was increased in tissues from PCa patients. Inhibition of IGHG1 by antibody blocking or genetic knockdown suppressed cell growth and induced cell cycle arrest and ultimate apoptosis. Expression levels of c-Myc were positively co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 31 publications
(39 reference statements)
1
17
0
Order By: Relevance
“…Previous studies have indicated that IGHG1 demonstrated promotive effects on tumor expansion in murine pancreatic cancer models [ 13 ]. Moreover, several studies on ovarian cancer, prostate cancer also indicated that IGHG1 promoted tumor migration and metastasis via modulating EMT [ 14 ] or MEK/ERK/c-Myc pathway [ 15 ]. Our study provided consistent results that IGHG1 significantly promoted proliferative and migrative capabilities of gastric cancer cells, which could be potential therapeutic target in future treatment development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that IGHG1 demonstrated promotive effects on tumor expansion in murine pancreatic cancer models [ 13 ]. Moreover, several studies on ovarian cancer, prostate cancer also indicated that IGHG1 promoted tumor migration and metastasis via modulating EMT [ 14 ] or MEK/ERK/c-Myc pathway [ 15 ]. Our study provided consistent results that IGHG1 significantly promoted proliferative and migrative capabilities of gastric cancer cells, which could be potential therapeutic target in future treatment development.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was reported that IGHG1 could induce EMT in gastric cancer cells by regulating TGF-β/SMAD3 signaling pathway [ 16 ], which is in line with our study. Meanwhile, inhibition of IGHG1 restrained the tumor growth in nude mice and inactivated MEK/ERK/c-Myc pathway [ 15 ]. Suppression of IGHG1 leaded to growth inhibition and apoptosis induction in human prostate cancer cell [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The protumorigenic roles of secreted cancer-derived IgG can be blocked by its specific monoclonal antibody RP215. In another study, the MEK/ERK/c-Myc pathway was demonstrated to be another downstream pathway of cancer-derived IgG regulating cell growth and the cell cycle ( 83 ). Moreover, Igκ and Igλ have been shown to be responsible for maintaining high expression of the antiapoptotic molecule Bcl-xL and thus perform roles in resisting apoptosis ( 84 ).…”
Section: Cancer-derived Ig Performs Critical Roles In Cancer Progressmentioning
confidence: 99%
“…The role of IGHG1 in CRC has never been investigated. In prostate cancer research, inhibition of IGHG1 can suppress cell growth and induce cell cycle arrest and ultimate apoptosis [ 24 ].…”
Section: Discussionmentioning
confidence: 99%